Comparative Evaluation of the Electronic Residency Application Service Versus the Plastic Surgery Common Application to a Single Institution in the 2022 Integrated Plastic Surgery Match. Issue 4 (15th April 2023) - Cordero, Justin J.; Kondra, Katelyn; Etemad, Shervin; Swerdlow, Mark; Yenikomshian, Haig; Carey, Joseph N.
Abstract : Background: The Plastic Surgery Common Application (PSCA) has emerged as a low-cost alternative application portal to the Electronic Residency Application Service (ERAS) for integrated plastic surgery applicants. During the 2021 to 2022 application cycle, our plastic surgery residency program accepted both the PSCA and ERAS applications to help recruit candidates otherwise deterred by prohibitively high application costs. We sought to determine how the PSCA compared with the ERAS application in a standardized review of applications scores. Methods: The PSCA and ERAS applications from 28 candidates who received interviews from the Keck School of Medicine were analyzed. These 56 applications were randomly assigned across 22 independent reviewers. Each reviewer scored applications on a scale of 1 to 5 with regard to communication skills, leadership, intellectual curiosity, compatibility with the program, service, and perseverance. Mean scores between the applications were compared using 2-tailed z tests, with statistical significance set at P < 0.05. Results: The 56 residency applications had a combined mean score of 4.21 (95% confidence interval [CI], 4.13–4.29). The mean score of PSCA applications (4.19; 95% CI, 4.08–4.31) did not significantly differ from the mean score of ERAS applications (4.24; 95% CI, 4.12–4.35; P = 0.57). The PSCA and ERAS applications did not have a significant difference in the mean scores for any review category. Conclusion: There was no difference between the overall scores and the scores of each review category between the PSCA and ERAS applications, suggesting that the PSCA may be a reasonable alternative to ERAS for medical students applying to plastic surgery residency.